The role of KRAB-ZFPs in transposable element repression and mammalian evolution - Yang, Peng (Trends Genet, 2017)
Kruppel-associated box zinc finger proteins (KRAB-ZFPs) make up the largest family of transcription factors in humans. These proteins emerged in the last common ancestor of coelacanth and tetrapods and have expanded and diversified in the mammalian lineage. Although their mechanism of transcriptional repression has been well studied for over a decade, the DNA binding activities and the biological function of these proteins has been largely unexplored. Recent large scale ChIP-seq studies and loss-of-function experiments have revealed that KRAB-ZFPs play a major role in the recognition and transcriptional silencing of transposable elements (TEs), consistent with an “arms race model” of KRAB-ZFP evolution against invading TEs. However, this model is insufficient to explain the evolution of many KRAB-ZFPs that appear to domesticate TEs for novel host functions. We highlight some of the mammalian regulatory innovations driven by specific KRAB-ZFPs, including genomic imprinting, meiotic recombination hotspot choice, and placental growth.